2021
DOI: 10.4269/ajtmh.20-1262
|View full text |Cite
|
Sign up to set email alerts
|

Case Report: Ischemic Colitis in Severe COVID-19 Pneumonia: An Unforeseen Gastrointestinal Complication

Abstract: Clinical manifestations and complications of SARS-CoV-2 are still emerging and variant. Gastrointestinal (GI) manifestations and complications are hugely under-recognized. The presence of angiotensin converting enzyme-2 receptors in the intestinal enterocytes, the receptors primarily involved in the pathogenesis of COVID-19 pneumonia, maybe the key factor contributing to the pathogenesis of GI manifestations. Ischemic colitis, although the most common ischemic pathology of the GI tract, is relatively rare, occ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(28 citation statements)
references
References 22 publications
(21 reference statements)
0
27
0
1
Order By: Relevance
“…Ischemic colitis as a consequence of COVID-19 appears to occur in patients presenting with severe respiratory illness. Of the six cases available in the literature, four died as a result of ischemic colitis, and those that did survive either received tocilizumab [ 16 ] or underwent the creation of an ostomy in order to prevent perforation [ 17 ]. The mechanism for the development of ischemic colitis in COVID-19 seems multifaceted.…”
Section: Discussionmentioning
confidence: 99%
“…Ischemic colitis as a consequence of COVID-19 appears to occur in patients presenting with severe respiratory illness. Of the six cases available in the literature, four died as a result of ischemic colitis, and those that did survive either received tocilizumab [ 16 ] or underwent the creation of an ostomy in order to prevent perforation [ 17 ]. The mechanism for the development of ischemic colitis in COVID-19 seems multifaceted.…”
Section: Discussionmentioning
confidence: 99%
“…Chan et al [13] were the first to report a case of SARS-CoV-2 infection causing ischemic colitis with high D-dimer levels and inflammatory markers, together with clinical and radiographic findings of Similarly, Paul et al [14] reported a case of severe COVID-19 pneumonia, developing ischemic colitis.…”
Section: Discussionmentioning
confidence: 99%
“…Norsa et al [ 69 ] also suggested that a high level of suspicion for intestinal ischemia should be maintained in COVID-19 patients presenting with GI symptoms or with arising abdominal pain because this complication could account for an increase mortality risk. Paul et al [ 70 ] discussed a case of severe COVID-19 pneumonia, developing ischemic colitis, for several reasons, including hypercoagulable state, coagulopathy leading to thromboembolic complications, and use of vasopressors in severely ill patients with hemodynamic compromise. Singh et al [ 71 ] conducted a rapid review of the current scientific literature available in PubMed to identify cases of acute mesenteric ischemia (AMI) in COVID-19 patients, and they summarized the clinical characteristics of COVID-19 patients with AMI.…”
Section: Digestive System Manifestations In Covid-19 Patientsmentioning
confidence: 99%